Tourism Development Challenges in the Era of Globalization: Maintaining the Archipelago’s Insights and Pancasila’s Morals - Aqueena Janette Putri Riyadi; Maulia Depriya Kembara; Najwati Yanis; Hany Sekar Maulida Wijaya (Language Assistance, 2025)
Globalization has significantly influenced local cultural values and triggered a national identity crisis in the development of Indonesia’s tourism sector. This article aims to explore the correlation between globalization, national identity, and tourism development that is built upon national values. It analyzes the roles of Wawasan Nusantara (archipelago insight) and Pancasila morals as ethical foundations for sustainable tourism and culturally grounded tourism. Utilizing a qualitative method through literature review, the study examines scholarly sources concerning nationalism, development ethics, tourism strategies, and the cultural impacts of globalization. The findings reveal a gap between modern tourism strategies and the preservation of cultural and moral values. This article underscores the importance of integrating national insight and Pancasila morals as foundational elements in tourism development. It is hoped that this research provides valuable insights for industry practitioners and academics in fostering tourism that not only stimulates economic growth but also strengthens national identity in the face of globalization in Indonesia.